Characterization of the Transforming Poteins of Adenovirus Type 5 Synthesized in Infected Human Cells and Transformed Hamster Cells - Rowe, David T. (My University, 1983)
It is known that human adenovirus type 5 gene products will cause the conversion of primary cells to a potentially oncogenic state. The transforming gene resides in a 4050 base pair (bp) region (early region 1; E1: 0-11.2 map units, mu) at the left end of the physical map of the linear duplex DNA genome (ca. 37,000 bp). Early region 1 is organized into two transcription units, E1A (0-4.5 mu) and E1B (4.5-11.2 mu), each of which produces multiple species of mRNAs and polypeptides. The results of studies on a libraryof baby hamsters kidney cell lines transformed by the adenoviral DNA fragments representing all (XhoI C:0-16 mu) or only a part (Hind III G:0-8 mu) of E1 established that the E1-58 product was unnecessary for both maintenance of the transformed state and oncogenicity. It was further shown that although mutants defective for 58K expresion are transformation deficient in the virion mediated transformation assays, the DNA extracted from these mutant viruses possessed transforming activity comparable to wt in in vitro DNA transfection assays. The mutant transformed hamster cells lines which emerged from these experiments fid not express the 58K product but exhibited a range of oncogenic potentials in newborn hamsters similar to wt transformed lines.
Hamster anti-tumor serum and a rabbit serum specific for a synthetic peptide corresponding to the carboxy terminus of the E1A proteins were used to identify E1A proteins (52K, 50K. 48.5K, 37.5K, 35K, 29K, AND 25K) and E1B proteins (19K and 58K) in infected and transformed cells. Interestingly, the few batches of anti-tumor sera positive for E1A products all recognized only a subset (52K, 48.5K, 37.5K) of the E1A proteins corresponding to the products of only the largest of the E1A mRNAs. These immunoreagents were used to study the deposition of transforming proteins by cell fraction and indirect immunofluoresence techniques. The E1B-19K was resolved into two related cytoplasmic membrane associated polypeptides (19K and 18.5K) neither of which were detected on the outer surface of the plasma membrane. The E1B-58K appeared to accumulate in the nucleus during the lytic cycle. E1A products localized in both nuclear and cytoplasmic compartments and, within the cytoplasm, these proteins showed a marked affinity for the cytoskeleton.
By examining the kinetics of early protein synthesis during lytic infection of KB cells by wild type (wt), it was shown that E1A, E1B, E2 (61.6-74.9 mu) and E4 (91.4-99.1 mu) proteins were expressed in a temporal relationship. Infectious with the E1A host range (hr) mutant hr3 were characterized by severely depressed levels of early protein synthesis consistent with the proposed role of E1A gene products as activators of early transcription units. The normal pattern of expression was also perturbed by a defect in E1B as the E1B host range mutant hr6 showed generally delayed and reduced levels of early gene expression suggesting a role for E1B gene products in the efficient expression of early genes.
Keywords: Biology; Biology